2004
DOI: 10.1248/bpb.27.1611
|View full text |Cite
|
Sign up to set email alerts
|

Melanogenesis Stimulation in Murine B16 Melanoma Cells by Piper nigrum Leaf Extract and Its Lignan Constituents

Abstract: A methanolic extract from the leaves of Piper nigrum L. showed a significant stimulatory effect on melanogenesis in cultured murine B16 melanoma cells. Activity-guided fractionation of the methanolic extract led to the isolation of two known lignans, (؊)-cubebin (1) and (؊)-3,4-dimethoxy-3,4-desmethylenedioxycubebin (2), together with a new lignan, (؊)-3-desmethoxycubebinin (3). Among these lignans, 1 and 2 showed a significant stimulatory activity of melanogenesis without any significant effects on cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 16 publications
3
28
0
Order By: Relevance
“…The results concerning the melanogenesis activities of sixteen coumarins (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) are shown in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results concerning the melanogenesis activities of sixteen coumarins (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) are shown in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…For the development of gray hair prevention agents, we have carried out a screening program to find a potential stimulant of melanogenesis from natural resources by using cultured murine B16 melanoma cells with theophylline as a reference drug. In a preceding paper, 3) we reported that a methanolic extract from the leaves of Piper nigrum L. showed a significant stimulatory effect on melanogenesis in cultured murine B16 melanoma cells and that two lignans, (Ϫ)-cubebin and (Ϫ)-3,4-dimethoxy-3,4-desmethylenedioxycubebin, were isolated as its active constituents. As the next step in our herbal screening, we report here the melanogenesis stimulation effect of seven ethanolic extracts obtained from Umbelliferae -dokkatsu), and the fruits of Cinidium monnieri (L.) CUSSON (Jashoshi) and C. formosanum YABE (Taiwan-jashoshi).…”
mentioning
confidence: 98%
“…Ref. ;Matsuda et al, 2004) Melanocytes or Melanoma cells Melanogenesis stimulating agents were found during the course of the screening using B16 melanoma cells for cosmetic ingredients with melanogenesis inhibitory activity. Some of the stimulation agents that originated in Piper plants may be useful as cosmetic ingredients for prevention of gray hair after further experimental studies, including clinical trials.…”
Section: Melanin Content (µG/well)mentioning
confidence: 99%
“…The cell proliferation of B16 cells was assessed according to the method as described previously. 7) Cell proliferation was shown in percentages. Each percentage in the treated cells was calculated with respect to that of the vehicle control cells.…”
mentioning
confidence: 99%